2018
DOI: 10.1002/nag.2887
|View full text |Cite
|
Sign up to set email alerts
|

Modeling soil desiccation cracking by analytical and numerical approaches

Abstract: Summary An energy approach is proposed as a complement to the stress approach commonly considered for investigating soil desiccation cracking. The elastic strain energies before and after crack initiation are estimated by both numerical and analytical solutions. The energy released by cracking is then compared with the fracture energy to discuss crack initiation conditions. This leads to combined energy and stress conditions for crack initiation following Leguillon's theory. An approximate analytical solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Furthermore, it should be pointed out that the frictional force triggered requires a relative move tendency between the contact objects and thus relates to the shrinkage of soil adjacent to the base. Due to the gradient of evaporation along the soil profile during the drying process (An et al, 2018; Hillel, 1982; Pouya et al, 2018; Wilson et al, 1997), it takes some time for the evaporation to affect the water content of the subsoil, induce the subsoil shrinkage, and then trigger the effect of basal friction. For the relatively thicker soil sample, it takes more time to trigger the basal friction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it should be pointed out that the frictional force triggered requires a relative move tendency between the contact objects and thus relates to the shrinkage of soil adjacent to the base. Due to the gradient of evaporation along the soil profile during the drying process (An et al, 2018; Hillel, 1982; Pouya et al, 2018; Wilson et al, 1997), it takes some time for the evaporation to affect the water content of the subsoil, induce the subsoil shrinkage, and then trigger the effect of basal friction. For the relatively thicker soil sample, it takes more time to trigger the basal friction.…”
Section: Discussionmentioning
confidence: 99%
“…The frictional force generated on the base between soil interlayers applies a significant constraint to the upper soil shrinkage and causes the soil desiccation cracking. In previous studies, some scholars found that the basal friction could affect the stress distribution inside the soil and aggravate soil cracking (Amarasiri & Kodikara, 2013;Gui et al, 2016;Guo et al, 2018;Lakshmikantha et al, 2018;Pouya et al, 2018;Rodríguez, 2006;Sima et al, 2014;Vo et al, 2017;Zeng et al, 2019). So far, most prior studies focus on the evolutions of desiccation cracks initiated at the soil top surface.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to replicate the complex cracking dynamics and interpret the governing mechanisms, numerical models based on soil hydro‐mechanical constitutive laws have been developed (Amarasiri et al., 2011; Amarasiri & Kodikara, 2013; Gui et al., 2016; Guo et al., 2018; Kodikara et al., 2004; Pouya et al., 2019; Rodríguez et al., 2007; Sánchez et al., 2014; Vo et al., 2017). The modellings revealed that individual crack propagation depends on the stress/strain concentration in local soil bodies (Lin et al., 2021; Pouya et al., 2019; Sánchez et al., 2014). This outcome was further confirmed in soil desiccation experiments at the laboratory scale, where the progression of individual crack branches was traced using precise image analysis techniques such as Digital Image Correlation (DIC) and Particle Image Velocimetry (PIV) (Li et al., 2019; Trabelsi et al., 2018; Wang et al., 2018; Wei et al., 2016; Zeng et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the challenge remains in finding the best way to model water movement in soils dominated by macropores that cannot be included by averaging nor fit in the capillary modeling concept. There are several studies that aim at developing this type of models (Pouya, 2015; Pouya et al., 2019; Walton et al., 2019), but their implementation requires explicit dense discretization of the matrix and fractures domains mesh, making them computationally unfeasible for representing systems which are larger than a few fractures.…”
Section: Introductionmentioning
confidence: 99%